2008
DOI: 10.21273/hortsci.43.3.862
|View full text |Cite
|
Sign up to set email alerts
|

Rye Mulch Management Affects Short-term Indicators of Soil Quality in the Transition to Conservation Tillage for Cabbage

Abstract: If benefits of conservation tillage can be quantified even in the transition year from conventional tillage, growers will more likely integrate practices that maintain or enhance soil quality and productivity. The management of surface residue is an important component of conservation tillage, especially in cool, rainy climates where vegetable growth and yield reductions have been observed when heavy residue is present. Cereal rye (Secale cereale L.), grown until flowering, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Cabbage biomass and yields, midseason and at-harvest respectively, were reduced because of interactions between cabbage, weeds, and oats in 2010. Other studies also have observed cabbage yield reductions in killed oat plots (Bottenberg et al 1997, Mochizuki et al 2008. Further studies are needed to determine management strategies that improve arthropod management although minimizing weed and cover crop interference with the crop.…”
Section: Discussionmentioning
confidence: 99%
“…Cabbage biomass and yields, midseason and at-harvest respectively, were reduced because of interactions between cabbage, weeds, and oats in 2010. Other studies also have observed cabbage yield reductions in killed oat plots (Bottenberg et al 1997, Mochizuki et al 2008. Further studies are needed to determine management strategies that improve arthropod management although minimizing weed and cover crop interference with the crop.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported improved yields and/or profitability of ST relative to both no tillage (NT) or FWT in many crops (Hoyt et al, 1996;Lonsbary et al, 2004;Luna and Staben, 2002;Luna et al, 2012;Mochizuki et al, 2007;Mochizuki et al, 2008;Wang and Ngouajio, 2008), although reductions in crop yields in ST compared to FWT have been observed in some cases (Bryant et al, 2013;Hoyt, 1999). In snap beans, yield responses to tillage have 22 | B r a i n a r d e t a l .…”
Section: Crop Yield and Harvest Indexmentioning
confidence: 99%
“…Battles are currently being waged in California over its use [10]. However, if land and/or time are available to a grower, crop rotation can provide many of the beneficial effects of fumigation and impact the soil community [12,14]. Mustards (Brassica sp.…”
Section: Opportunitiesmentioning
confidence: 99%